Brain functional characteristics in football players during motor-cognitive dual task: insights from fNIRS - Yin, J.; Gao, S.; Zhang, M.; Xu, G.; Xu, K.; He, X.; Wang, Y.; Li, Z.; Shao, B. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Long-term training enables professional athletes to develop concentrated and efficient neural network organizations for specific tasks. This study used functional near-infrared spectroscopy to investigate task performance, brain functional characteristics, and their relationships in footballers during sport-specific motor-cognitive processes. Twenty-four footballers (athlete group, with 18 remaining of good signal quality) and 20 non-footballers (control group, with 16 remaining) completed four tasks: a single task (trigger buttons corresponding to the appearance direction of teammates with kicking actions), an N-back direction task, a dual task, and an N-back digit task. Brain activation, functional connectivity (FC), and lateralization were calculated, and their correlation with behavioral indicators was analyzed. Results showed that reaction times were shorter in footballers across all tasks. The activation value in the right dorsolateral prefrontal cortex (DLPFC) decreased during dual task compared to the resting state in the athlete group. The activation values in all brain regions (except left primary sensory cortex in the single task), right DLPFC (dual task), and left premotor cortex & left supplementary motor area (left PMC & left SMA, digit task) were significantly lower in the athlete group than in the control group. Footballers exhibited higher interhemispheric FC during the direction and digit tasks, and greater leftward bias in the DLPFC during the dual task. The FC between left prefrontal cortex (PFC) -left PMC & left SMA and within the left PFC region was significantly positively correlated with accuracy during the dual task. Footballers showed better task performance with less impact from load, lower central energy consumption and higher sensory-motor network connectivity during task execution, indicating a more efficient state. Enhancing brain function and related networks may improve athletes' reactive abilities and performance.